The zone 2 concept and distal stent graft positioning in TH 2–3 are associated with high rates of secondary aortic interventions in frozen elephant trunk surgery. (17th April 2021) - Liebrich, Markus; Charitos, Efstratios I; Schlereth, Sebastian; Meißner, Helfried; Trabold, Tobias; Geisbüsch, Philipp; Hemmer, Wolfgang; Seeburger, Joerg; Voth, Vladimir
Abstract:  : OBJECTIVES: The goal of this study was to investigate the association between the localization of the distal anastomosis (zone 2/3), the stent graft length (100–160 mm), the position of the distal end of the hybrid prosthesis and the need for secondary aortic intervention (SAI) in acute and chronic thoracic aortic disease after the frozen elephant trunk procedure. METHODS: From 2009 through 2020, a total of 232 patients (137 men; mean age, 61.7 ± 13.8 years) were treated with the frozen elephant trunk procedure. The main indications were acute aortic dissection type A ( n  = 106, 46%), chronic aortic dissection type A ( n  = 52, 22%) and degenerative thoracic aortic aneurysm ( n  = 74, 32%). RESULTS: The rate of SAI was significantly higher when we performed a distal anastomosis in zone 2 rather than in zone 3, whereas the rate of SAI was less frequent if the distal positioning of the hybrid prosthesis was below TH 4–5. Combining the zone 2 concept and the short stent graft length (100 mm) was associated with a significantly higher rate of SAIs. Patients with a distal anastomosis in zone 2 were significantly less likely to have a recurrent laryngeal nerve injury ( P  < 0.001). However, no association between a specific arch zone of a distal anastomosis and the occurrence of spinal cord injury was observed. CONCLUSIONS: Rates of SAIs are highest in patients who were treated with a distal anastomosis in zone 2 and a short stent graft (100 mm) with the distal end of the hybrid prosthesis at vertebral level TH 2–3.